2008
DOI: 10.1007/978-0-387-09686-5_6
|View full text |Cite
|
Sign up to set email alerts
|

A Unified Approach to Computing Real and Complex Zeros of Zero-Dimensional Ideals

Abstract: Abstract. In this paper we propose a unified methodology for computing the setWe show how moment matrices, defined in terms of a given set of generators of the ideal I, can be used to (numerically) find not only the real variety V R (I), as shown in the authors' previous work, but also the complex variety V C (I), thus leading to a unified treatment of the algebraic and real algebraic problem. In contrast to the real algebraic version of the algorithm, the complex analogue only uses basic numerical linear alge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…It has also been shown that the limit can even be reached in a finite number of steps in some cases, see e.g. (Lasserre et al, 2009;Nie et al, 2006;Marshall, 2009;Ha and Pham, 2010;Nie, 2011;Abril Bucero and Mourrain, 2013). In this case, the relaxation is said to be exact.…”
Section: Full Moment Matrix Relaxation Hierarchymentioning
confidence: 99%
See 4 more Smart Citations
“…It has also been shown that the limit can even be reached in a finite number of steps in some cases, see e.g. (Lasserre et al, 2009;Nie et al, 2006;Marshall, 2009;Ha and Pham, 2010;Nie, 2011;Abril Bucero and Mourrain, 2013). In this case, the relaxation is said to be exact.…”
Section: Full Moment Matrix Relaxation Hierarchymentioning
confidence: 99%
“…In this section we introduce the notion of optimal linear form for f , involved in the computation of I min (also called generic linear form when f = 0 in (Lasserre et al, 2009(Lasserre et al, , 2012). In order to find this optimal linear form we solve a Semi-Definite Programming (SDP) problem, which involves truncated Hankel matrices associated with the monomial basis and the reduction of their products by the border basis, as described in the previous section.…”
Section: Optimal Linear Formmentioning
confidence: 99%
See 3 more Smart Citations